2003
DOI: 10.1021/jp030430m
|View full text |Cite
|
Sign up to set email alerts
|

CO2 as a Probe for Monitoring the Surface Defects on TiO2(110)Temperature-Programmed Desorption

Abstract: The adsorption and thermal desorption of CO 2 bound to both oxidized and reduced TiO 2 (110) surfaces has been studied using temperature-programmed desorption. For the stoichiometric and fully oxidized surface, a single thermal desorption feature (E d ) 48.5 kJ/mol) is measured and attributed to CO 2 bound to regular fivefold coordinated Ti 4+ atoms. For the fully reduced TiO 2 (110) surface, CO 2 binds not only to regular sites, but also to oxygen vacancy sites (E d ) 54.0 kJ/mol), created by thermal annealin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
137
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(156 citation statements)
references
References 27 publications
17
137
2
Order By: Relevance
“…It revealed two desorption peaks at temperature ca. 175 and 200 K. Thomson et al [19] reported that surface of TiO 2 incorporates fivefold-coordinated Ti 4+ sites and fourfold-coordinated Ti 3+ sites. Based on their study, it was confirmed that the peak at ca.…”
Section: Resultsmentioning
confidence: 99%
“…It revealed two desorption peaks at temperature ca. 175 and 200 K. Thomson et al [19] reported that surface of TiO 2 incorporates fivefold-coordinated Ti 4+ sites and fourfold-coordinated Ti 3+ sites. Based on their study, it was confirmed that the peak at ca.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that CO 2 is a very useful probe molecule to distinguish pristine and defect sites on metal oxides [34][35][36]. For rutile TiO 2 (110), CO 2 adsorbs initially preferentially on defect sites as the highest binding energy sites.…”
Section: Data Presentation and Discussionmentioning
confidence: 99%
“…Surface defects such as oxygen vacancies tend to bind CO 2 more strongly than the regular surface, 13 and CO 2 adsorption can therefore be used as a quantitative probe of the defect concentration. 14 To date there are no investigations of CO 2 adsorption on well-defined iron-oxide surfaces, despite the important role of these materials in both geochemistry and catalysis. Work on polycrystalline Fe 3 O 4 , 15 Fe 3 O 4 nanoparticles, 16 and FeO x nanoclusters on graphite 17 suggests however that both physisorption and carbonate formation can a) E-mail address: parkinson@iap.tuwien.ac.at occur, with stronger binding linked to the presence of Fe 2+ cations.…”
Section: Introductionmentioning
confidence: 99%